The Educational Family In The Presence Of The Coronavirus Covid 19 The Studying Anthropology In The Educational Institution Mostaganem - Sheikh Djalloul Al-nasser Intermediate School As A Model - fakir, rachid (El Omda in Linguistics and Discourse Analysis, 2023)
Abstract : This study dealt with a research problem that relates to the social conditions that the professor lived in in the presence of the Corona virus, Covid 19. It means how the professor coexisted with the virus, and the latter is one of the coronaviruses that were named so because of their shape, and it is called the Corona pandemic according to some scientists So I entered Algeria and affected all areas in the Algerian state, including the economic, social and cultural ones, especially the education sector. In our study, we try to know the impact of the virus in the educational institution, so our anthropology research was in an educational institution in Algeria and was conducted between 2019 and 2020. Therefore, we concluded that the professor was greatly affected by the virus in all respects, and we also conclude that the exceptional curriculum has exhausted him on the one hand and on the other hand affected the academic achievement of students